1999
DOI: 10.1191/026765899676722648
|View full text |Cite
|
Sign up to set email alerts
|

Null anaphora in Spanish second language acquisition: probabilistic versus generative approaches

Abstract: The acquisition of Spanish null pronouns is an optimal domain for comparing the predictions of generativist vs. probabilistic approaches to language acquisition. This paper presents two studies on the acquisition of null subjects by English adult learners of Spanish as a second language. The first investigates a low frequency construction in which the antecedent of the pronoun is a quantifier, and the distribution is regulated by a principle of UG. The second looks at a high frequency context,where the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 22 publications
6
56
0
4
Order By: Relevance
“…Other factors that may affect bilinguals' mastery of constraints on omissions include dominant language transfer (Serratrice et al 2004;Sorace 2004;Tsimpli et al 2004), non-target-like mastery of pragmatic rules (Pérez-Leroux and Glass 1999;Rothman 2009, Ivanova-Sullivan 2014, and (for HL speakers) idiosyncratic properties of the baseline input grammar (Laleko 2010;Pires and Rothman 2009). While further studies are necessary to evaluate each of these factors experimentally, our data suggest some preliminary considerations.…”
Section: Unifying the Findings: Silence With Anaphoric Dependencies Imentioning
confidence: 86%
“…Other factors that may affect bilinguals' mastery of constraints on omissions include dominant language transfer (Serratrice et al 2004;Sorace 2004;Tsimpli et al 2004), non-target-like mastery of pragmatic rules (Pérez-Leroux and Glass 1999;Rothman 2009, Ivanova-Sullivan 2014, and (for HL speakers) idiosyncratic properties of the baseline input grammar (Laleko 2010;Pires and Rothman 2009). While further studies are necessary to evaluate each of these factors experimentally, our data suggest some preliminary considerations.…”
Section: Unifying the Findings: Silence With Anaphoric Dependencies Imentioning
confidence: 86%
“…1 Another aspect of L2 null and overt subject use that has been investigated in the past involves a comparison of the discourse-related properties of topic and focus. Though not using the term interfaces, Pérez-Leroux and Glass (1997Glass ( , 1999 do make explicit comparisons between the acquisition of purely syntactic or semantic constraints on overt pronouns versus choices affected by which NP is the topic or focus in the sentence. Using elicited production tasks (translation and question answering), they found that L2 learners of Spanish at all levels of proficiency appropriately used null pronouns instead of overt pronouns in bound variable contexts, which are governed by a universal constraint against overt pronouns (Montalbetti, 1984).…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Starting in the 1990s, a line of research in GenSLA concentrated on testing whether L2 learners did indeed acquire properties of the L2 incidentally and, specifically, if L2 learners acquire PoS properties. Early work such as that by Kanno (1997), Pérez-Leroux and Glass (1999), Dekydtspotter, Sprouse, and Anderson (1997), and Dekydtspotter, Sprouse, and Thyre (2000), among many others since, have showed that L2 grammars, despite significant differences from L1 grammars, instantiate universal linguistic properties that cannot be linked to transfer or accounted for by learning in the truest sense of the word (for an extended example, see the next section). Such evidence seriously questions any claims for a fundamental difference between L1 and L2 acquisition.…”
Section: The Main Tenets Of Genslamentioning
confidence: 99%